2014
DOI: 10.1002/ppap.201400108
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low Temperature Plasma against SCaBER Cancer Cells

Abstract: The efficacy of the plasma pencil is studied for its cancer therapeutics effects against the SCaBER cell line. First, the SCaBER cells in media were treated with different exposure times of low temperature plasma (LTP). Secondly, LTP activated media was generated by treating the media prior to adding it to the cells. Cell viability was assayed at 0, 24, 48, and 72 h after treatments. The results indicate that both treatments alter cell morphology, cell reattachment, and kill SCaBER cells in an exposure time de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 15 publications
1
40
0
1
Order By: Relevance
“…One such mode is caspase activation. Laroussi and co‐workers studied capse‐3 activation in the case of squamous cell carcinoma and found higher level of caspase‐3 activation in cancer cells treated by LTP than in control samples, indicating that LTP induces apoptosis in these cells. Ishaq et al suggested that because tumor cells are defective in several regulatory signaling pathways they exhibit metabolic imbalance, which leads to a lack of cell growth regulation.…”
Section: Mechanisms Of Action Of Ltp and Safety Issuesmentioning
confidence: 99%
“…One such mode is caspase activation. Laroussi and co‐workers studied capse‐3 activation in the case of squamous cell carcinoma and found higher level of caspase‐3 activation in cancer cells treated by LTP than in control samples, indicating that LTP induces apoptosis in these cells. Ishaq et al suggested that because tumor cells are defective in several regulatory signaling pathways they exhibit metabolic imbalance, which leads to a lack of cell growth regulation.…”
Section: Mechanisms Of Action Of Ltp and Safety Issuesmentioning
confidence: 99%
“…1,2 Several investigators used PAM successfully and showed that it has killing and anti-proliferative effects against various cancers including ovarian cancer, gastric cancer, glioblastoma, and breast cancer. [1][2][3][4][5] Therefore, using PAM can be a practical alternative for treating cancerous lesions since PAM has been shown to remain effective after a relatively long time of storage (hours to days depending on storage temperature).…”
Section: Introductionmentioning
confidence: 99%
“…After LTP exposure and proper incubation process (37 ℃ under 5% CO2 atmosphere), Trypan-blue exclusion assay was used to count the number of live and dead cells. For details of the experimental protocol please refer to [40]. The counts immediately after LTP treatment (at 0 h) revealed no dead cells, which suggested there were no immediate physical …”
Section: Two Biomedical Applications Of Ltpmentioning
confidence: 99%
“…This is an indication that plasma agents, such as reactive species and electric fields, interact with the cells and induce reactions and/or trigger biochemical pathways that ultimately result in the death of the cancer cells hours later. [40]. Figure 7 shows the selective effect of LTP when it comes to destroying cancer cells versus healthy cells in vitro.…”
Section: Two Biomedical Applications Of Ltpmentioning
confidence: 99%